2013 Curriculum Adaptation During Pandemic in Kindergarten Institutions in Ogan Ilir District, South Sumatera - Novita Loka (UPI Kampus Cibiru, 2022)
The purpose of the study was to determine the adaptation of the 2013 PAUD curriculum during the pandemic at the Kindergarten in Ogan Ilir Regency, South Sumatra. The data collection technique is a questionnaire through Google from several 20 teachers as respondents. The data analysis technique used is Miles and Huberman with three stages to go through. The stages are data collection, data reduction, and conclusions. The data obtained were tested for credibility using triangulation techniques. The results showed that the 2013 PAUD curriculum in Ogan Ilir underwent a significant adaptation. The adaptation includes learning references, learning materials, as well as learning processes and assessments that are used while continuing to use the 2013 PAUD curriculum and Permendikbud 146 of 2014. During the COVID-19 pandemic, learning carried out in Ogan Ilir Regency Kindergarten follows a limited face-to-face learning policy. In practice, students are divided into two groups in two learning sessions. The purpose of this policy is to stop the spread of covid 19. During the pandemic, students are given learning assignments to do at home. Thus the adaptation of the 2013 PAUD curriculum during the pandemic at the Kindergarten in Ogan Ilir Regency continues to run well but experiences innovation in the learning process. This innovation has a significant impact on the development of early childhood education in the Ogan Ilir Regency, such as giving freedom to children to develop their potential through activities carried out at school.